2008
DOI: 10.1103/physrevb.78.125411
|View full text |Cite
|
Sign up to set email alerts
|

Charge noise in single-electron transistors and charge qubits may be caused by metallic grains

Abstract: We report on measurements of low-frequency noise in a single-electron transistor ͑SET͒ from a few hertz up to 10 MHz. Measurements were done for different bias and gate voltages, which allow us to separate noise contributions from different noise sources. We find a 1 / f noise spectrum with two Lorentzians superimposed. The cut-off frequency of one of the Lorentzians varies systematically with the potential of the SET island. Our data is consistent with two single-charge fluctuators situated close to the tunne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
2
25
1
Order By: Relevance
“…4 and Table II, we show the reproducibility of these features across thermal cycles. Collectively, we find switching rates ranging from 71.4 µHz to 1.9 mHzslower than those obtained by measurements of charge noise [37] but similar to bulk-TLS dynamics [38,39] and in agreement with rates determined from measurements tracking the time evolution of individual TLS [17]. These measurements demonstrate not only that superconducting qubits are useful probes of TLS, but unambiguously demonstrate the role of a TLS-based Lorentzian noise profile as a limiting factor to the temporal stability of qubit coherence.…”
Section: Decoherence Benchmarkingcontrasting
confidence: 63%
See 1 more Smart Citation
“…4 and Table II, we show the reproducibility of these features across thermal cycles. Collectively, we find switching rates ranging from 71.4 µHz to 1.9 mHzslower than those obtained by measurements of charge noise [37] but similar to bulk-TLS dynamics [38,39] and in agreement with rates determined from measurements tracking the time evolution of individual TLS [17]. These measurements demonstrate not only that superconducting qubits are useful probes of TLS, but unambiguously demonstrate the role of a TLS-based Lorentzian noise profile as a limiting factor to the temporal stability of qubit coherence.…”
Section: Decoherence Benchmarkingcontrasting
confidence: 63%
“…5d-f). Typically, dephasing is thought to arise due to excess photons within the cavity [9,43], flux noise [25], charge noise [34,37], quasiparticles tunnelling through the Josephson junctions [32], or the presence of excess quasiparticles [44]. For qubit A, the charge dispersion is calculated to 524 Hz, much smaller than most of the observed frequency shifts.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was recently investigated in Ref. 17 where it was shown that such flakes located close to the tunnel junctions may act as two-level fluctuators. Taking into account reflections and quantum efficiency for current generation in the junction area, we estimate the number of charge transfers to be ഛ0.1 e / s for incident flux ഛ10 photons s −1 nm −2 .…”
Section: Resultsmentioning
confidence: 96%
“…Each impurity produces a bistable fluctuation of the island polarization. The collective effect of an ensemble of these random telegraph processes, with a proper distribution of switching rates, gives rise to 1/f -noise [20] routinely observed nanodevices [17,18,19].…”
Section: Introductionmentioning
confidence: 99%